Comparative analysis of the effect of 4MATRIX with and without PRF on regeneration of infrabony periodontal pockets - Bylbyl Reçica; Dashnor Bukleta; Mirjana Popovska; Urim Tefiku; Jehona Ahmedi; David Stubljar (Elsevier, 2023)
Aim: The aim was to compare the effect in improvement of periodontal pocket depth (PPD) and clinical attachment level (CAL) between application of 4MATRIX and 4 MATRIX combined with PRF in advanced periodontal disease during follow-up of 6, 12 and 18 months. Methods: Thirty patients of both genders aged 25-50 years were included. The patients were clinically and radiologically diagnosed with generalized advanced chronic periodontitis with the presence of periodontal pockets with a depth of ≥ 5 mm bilaterally in the upper jaw. Both sides were treated with a flap intervention in all patients. On one side a bone substitute 4MATRIX was applied, and the other side was treated with an application 4MATRIX and PRF. The clinical assessment and measurements were performed in four stages, immediately before the intervention, and then 6, 12 and 18 months after the intervention. PPD and CAL were determined in all four timepoints. Results: PPD was the highest at zero time before the surgery for both groups and was 5.56 ± 0.28 mm. In the postoperative follow-up period, the PPD value decreased gradually with the lowest average value of 5.10 ± 0.18 mm after 18 months in Group I and 4.67 ± 0.13 mm in Group II (p < 0.001, respectively). Moreover, comparing the values of PPD at 6, 12 and 18 months after the surgery, a significant difference was found between the patients from the 4MATRIX vs 4MATRIX + PRF (p < 0.001 respectively). The postoperative follow-up period showed a decrease in CAL value with the lowest value after 18 months. A significant difference in CAL was found between the four measurement times (p < 0.001, respectively). The average level of CAL was the highest before surgical treatment in both groups. The intergroup analysis of CAL after 18 months in group I (4MATRIX) was 5.27 ± 0.17 mm and in group II 4.10 ± 0.14 mm (p < 0.001). Conclusion: Treatment of adult patients with advanced chronic periodontitis with periodontal pockets of ≥ 5 mm bilaterally in the upper jaw using 4MATRIX and 4MATRIX + PRF showed improvement of PPD and lower CAL loss after 18 months of the treatment. In the group treated with 4MATRIX + PRF patients showed the highest improvement in PPD and CAL loss. The analysis of treatment with 4MATRIX and 4MATRIX + PRF showed the lowest values after 18 months of the treatment.